Genetic polymorphisms of matrix metalloproteinase-9, tissue inhibitor of matrix metalloproteinase-1 and development of postoperative atrial fibrillation in elderly patients - A. O. Rubanenko; O. A. Rubanenko; L. V. Limareva; Iu. V. Shchukin (Российский кардиологический журнал)
Aim. The aim of the study was to assess the association of genetic polymorphisms of matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) with atrial fibrillation development in elderly patients with coronary artery disease (CAD), undergoing coronary artery bypass graft (CABG) surgery.Material and methods. Studied were 80 patients who underwent CABG in 2015-2016 years. In all the patients routine laboratory and instrumental tests were performed. Patients also underwent genetic polymorphisms of ММР-9 А8202G and TIMP-1 C536T estimation with polymerase chain reaction. According to occurrence of postoperative atrial fibrillation (POAF) all the patients were divided into two groups: 1 group comprised 56 patients without POAF (81,8% males, mean age 65,9±4,0 years), 2 group — 24 patients with first detected episode of AF after CABG (875% males, mean age 67,7±5,4).Results. According to results of multivariate regression analysis the odds ratio of POAF development in patients with stable angina grade III was 1,8 (95% CI 0,5-75, p=0,4), NYHA III — 0,85 (95% CI 0,2-3,5, p=0,55), history of CAD more than 20 months — 1,8 (95% CI 1,2-8,1, p=0,03), LA diameter more than 39 mm — 4,2 (95% CI 1,6-9,5, p<0,0001), allele G MMP-9 A8202G — 2,6 (95% CI 1,2-75, p=0,03). Conclusion. In elderly patients undergoing coronary artery bypass graft surgery left atrial diameter more than 39 mm, history of coronary artery disease more than 20 months and the presence of G allele of MMP-9 A820G are significantly associated with postoperative atrial fibrillation occurrence.